A 57‐bp deletion in the ovine KAP6‐1 gene affects wool fibre diameter. (17th March 2015) - Zhou, H.; Gong, H.; Li, S.; Luo, Y.; Hickford, J.G.H.
Summary High glycine–tyrosine keratin‐associated proteins (HGT‐KAPs) are predominantly present in the orthocortex of wool fibres. They vary in abundance in different wools and have been implicated in regulating wool fibre properties, but little is known about the functional roles of these proteins in the fibre matrix. In this study, we used polymerase chain reaction – single‐strand conformational polymorphism (PCR‐SSCP) analysis to screen for variation in a gene encoding the ovine HGT‐KAP6‐1 protein. We identified three gene variants (A, B and C). Variants A and B were similar to each other, with only three nucleotide differences occurring downstream of the coding sequence. However, variant C had a 57‐bp deletion that would notionally result in a loss of 19 amino acids in the protein. The presence of C was found to be associated with an increase in mean fibre diameter (MFD), fibre diameter standard deviation (FDSD), coefficient of variation of fibre diameter (CVFD) and prickle factor (percentage of fibres over 30 microns; PF). Sheep of genotype BC produced wool of greater MFD, FDSD and PF than sheep of genotypes AA, AB and BB. The CVFD was greater in the BC sheep than the AB sheep. The results suggest that variation in ovine KRTAP6‐1 affects wool fibre diameter‐associated traits and that the 57‐bp deletion in this gene would lead to coarser wool with greater FDSD, CVFD and PF.